2014
DOI: 10.1016/j.ygyno.2014.07.101
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II evaluation of ixabepilone (IND #59699, NSC #710428) in the treatment of recurrent or persistent leiomyosarcoma of the uterus: An NRG Oncology/Gynecologic Oncology Group Study

Abstract: Background The combination of gemcitabine and docetaxel is standard first-line therapy for recurrent or metastatic uterine leiomyosarcoma. There is no standard second-line therapy. Ixabepilone is a semi-synthetic analog of epothilone B that binds to the same site on beta tubulin as paclitaxel and may be a more potent polymerizer of tubulin. We sought to determine activity of ixabepilone as a single agent as second-line treatment for patients with metastatic uterine leiomyosarcoma who had received taxane based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Consistent with existing experience [32], we found that ixabepilone monotherapy had no activity in recurrent uterine leiomyosarcoma previously treated with a taxane.…”
Section: Clinical Outcomessupporting
confidence: 90%
“…Consistent with existing experience [32], we found that ixabepilone monotherapy had no activity in recurrent uterine leiomyosarcoma previously treated with a taxane.…”
Section: Clinical Outcomessupporting
confidence: 90%
“…Ixabepilone was studied by the NRG Oncology Group in a phase 2 trial and found not to be active as a single agent in uLMS [60]. Of 23 evaluable patients enrolled on the trial, only 4 patients (17.4%) had stable disease as best response to therapy.…”
Section: Targeted Agentsmentioning
confidence: 99%
“…In the present study, class III β-tubulin was not predictive of overall survival, perhaps due to the limited number of cases examined. Interestingly, a phase II study of ixabepilone, a microtubule-stabilizing agent which putatively overcomes taxane resistance conferred by upregulation of class III β-tubulin, showed no activity as a second-line agent in this disease [19], underscoring gaps in our current understanding of the biology of this disease and the persistent need for novel approaches to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Gemcitabine plus docetaxel currently represents one of the most effective cytotoxic combinations for this disease, with an overall response rate (ORR) of 27% [13]. Ifosfamide (ORR 17%) [14], pegylated liposomal doxorubicin (ORR 16%) [15], paclitaxel (ORR 8%) [16], oral etoposide (ORR 7%) [17], cisplatin (ORR 5%) [18], and ixabepilone (0% ORR) [19] have also been evaluated in patients. Adjuvant radiation therapy does not result in improved survival [20].…”
Section: Introductionmentioning
confidence: 99%